2014
DOI: 10.1259/bjr.20140428
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal displacement during course of adjuvant radiation for cervical cancer: results from a prospective IG-IMRT study

Abstract: Objective: To compare internal target volume (ITV) generated using population-based displacements (ITV_study) with empty and full bladder scan fusion (ITV_EBFB) for organ-at-risk (OAR) doses during adjuvant intensitymodulated radiation therapy (IMRT) for cervical cancer. Methods: From January 2011 to October 2012, patients undergoing IMRT were included. CT simulation was carried out after inserting vault markers. Planning target volume (PTV)_EBFB received 50 Gy per 25 fractions. Pre-treatment megavoltage CT (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Chopra et al 22 reported that 4.1 mm, 10.6 mm and 10.3 mm, for left-right, craniocaudal and AP margins respectively, could encompass 95% of the observed displacements. Shih et al 23 reported clinical outcomes in endometrial cancer and Folkert MR et al 24 in cervical cancer treated with adjuvant pelvic IMRT.…”
Section: Discussionmentioning
confidence: 98%
“…Chopra et al 22 reported that 4.1 mm, 10.6 mm and 10.3 mm, for left-right, craniocaudal and AP margins respectively, could encompass 95% of the observed displacements. Shih et al 23 reported clinical outcomes in endometrial cancer and Folkert MR et al 24 in cervical cancer treated with adjuvant pelvic IMRT.…”
Section: Discussionmentioning
confidence: 98%
“… 16 , 20 , 21 , 22 Translations exceeding 10 mm were more frequently observed in the posterior and superior directions, whereas smaller translations were observed in the right and left directions, consistent with previous findings. 23 , 24 Thus, the translations calculated using the algorithm were considered valid.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 However, the generation of ITV necessitates careful identification of targets on MVCT/KVCT scans. For the conduct of the present study, we hypothesized that the displacement characteristics of central recurrences may be different than that of uterus [21][22][23] and post-surgical vaginal remnant [24][25][26][27] and need prospective investigation. The methodology in the present study relied on evaluating COM displacement of recurrent tumour on daily MVCT images.…”
Section: Discussionmentioning
confidence: 99%